Knowledge, attitudes, and practices toward Mpox and vaccination: a cross-sectional study in Saudi Arabia - Amal K. Suleiman (Libyan Journal of Medicine)
Mpox is re-emerging globally and poses a growing public health threat, particularly in nonendemic countries such as Saudi Arabia. Given the limited national research on this topic, this study aimed to assess public perceptions, knowledge, and willingness to receive Mpox vaccination among the Saudi population. A cross-sectional online survey was conducted between March and August 2024 using a self-administered questionnaire adapted from previous studies. Participants aged 18 years and older residing in Saudi Arabia were included. Incomplete responses were excluded. Data were analyzed using Epi Info 7.2, employing descriptive statistics and Fisher’s exact test to evaluate associations (p < 0.05 considered significant). A total of 2847 complete responses were received (response rate: 94.9%). Among respondents, 71.0% reported being aware of Mpox, while 47.1% had received information on how the virus spreads. Non-Saudi residents represented 61.1% of the sample. The most frequently cited information sources were social media and websites (54.2%), followed by word-of-mouth (22.3%), traditional media (18.5%), and healthcare workers (5.0%). A substantial proportion (93.2%) reported a lack of awareness regarding preventive measures, and 67.3% expressed hesitancy toward Mpox vaccination. These findings reveal significant gaps in knowledge and preparedness concerning Mpox among the population in Saudi Arabia. Strengthening public education and enhancing communication through reliable health sources are essential to improve awareness and support future vaccination efforts.